Stigma Remaja terhadap ODHA Studi terhadap pelajar SMA di wilayah Jakarta Timur - Suhana Haeriyanto; Ni Luh Putu Ekarini; Dewi Lusiani (Poltekkes Kemenkes Jakarta III, 2019)
Stigma and discrimination against people with HIV/AIDS (PLWHA) is one of the obstacles in controlling the disease. Stigma and discrimination are carried out by ordinary people, including high school students who do not have sufficient knowledge about HIV / AIDS and a lack of attitudes towards disease recognition programs. The research aims to prove that knowledge can influence high school students in behaving against ODHA, and stima. By using a quasi-experimental design (pretest-posttest control group design) the study was conducted on 88 samples selected using a combination of randomized sampling to determine selected schools and non-randomized consecutive sampling to determine the selected sample units and determine the intervention group and control group. The results showed that there were differences in the average stigma score between the pretest and posttest in the intervention group (p = <0.005), so it could be concluded that knowledge was proven to have an effect on the stigma of students towards PLWHA.